2014
DOI: 10.1155/2014/139897
|View full text |Cite
|
Sign up to set email alerts
|

Bicondylar Hoffa Fracture Successfully Treated with Headless Compression Screws

Abstract: Bicondylar coronal plane fracture, eponymically named Hoffa fractures, is an extremely rare injury. We present a case of isolated unilateral bicondylar Hoffa fracture that was successfully treated with open reduction and internal fixation using headless compression screws with satisfactory results. We inserted posteroanteriorly oriented Acutrak screws perpendicular to the fracture plane via lateral parapatellar arthrotomy, which provided excellent compression across the fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
13
0
3
Order By: Relevance
“…The specific mechanism of a Hoffa fracture is not well understood. [12,13] Most researchers [2,7,14] currently believe that when the knee is in ≥90° of flexion and emergency braking is performed while driving a car, an axial force in either a varus or valgus direction is transferred from the proximal femur to the femoral condyle. At the same time, forces on the distal tibia are transferred to the tibial plateau, resulting in great shear stress between the femoral condyle and the tibial plateau.…”
Section: Injury Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific mechanism of a Hoffa fracture is not well understood. [12,13] Most researchers [2,7,14] currently believe that when the knee is in ≥90° of flexion and emergency braking is performed while driving a car, an axial force in either a varus or valgus direction is transferred from the proximal femur to the femoral condyle. At the same time, forces on the distal tibia are transferred to the tibial plateau, resulting in great shear stress between the femoral condyle and the tibial plateau.…”
Section: Injury Mechanismmentioning
confidence: 99%
“…For bicondylar Hoffa fractures, it is necessary to simultaneously expose both condyles [71] to allow proper reduction. Lee et al [13] reported that Gerdy osteotomy combined with an anterior lateral parapatellar approach provides appropriate exposure for bicondylar Hoffa fractures. Fixation with an anti-glide plate on the lateral condyle and tibial osteotomy with two 4.5-mm screws is ideal.…”
Section: Treatmentmentioning
confidence: 99%
“…Although Hoffa fractures are typically fixed with AP-oriented screws, Jarit et al, showed that fixation with posteroanteriorly-(PA-) oriented lag screws was biomechanically superior to AP oriented lag screws when subjected to vertical loads. 4 The standard method of fixing these fractures is using cannulated screws in compression mode. However as these are shear fractures, the parallel screw configuration sometimes leads to fixation failure.…”
Section: Case Reportmentioning
confidence: 99%
“…One advantage of using these screws is that compression along the entire length of the screw can be achieved, possibly resulting in improved stability compared with a conventional lag screw. 4…”
Section: Case Reportmentioning
confidence: 99%
“…Although the most common mechanism of Hoffa fracture injury is high energy trauma, but the specific mechanism of injury is still unknown. Lewis et al, suggested that axial load to the femoral condyle when the knee is flexed to >90° produces posterior tangential fractures [ 5 ]. There are some difficulties in diagnosis of unicondylar Hoffa fractures because of its poor visibility on standard X-rays especially in non-displaced fractures [ 6 ], so they may be missed.…”
Section: Introductionmentioning
confidence: 99%